Multiple-Clones of Streptococcus agalactiae harbouring lnuB gene - Faccone, Diego; Lalonardi, Florencia; Abel, Sofia; Machain, Monica; Errecalde, Laura; Littvik, Ana; Kauffman, Sara; Galas, Marcelo; WHONET-Argentina, Group; Corso, Alejandra (The Journal of Infection in Developing Countries, 2010)
Six S. agalactiae displaying an L-phenotype were recovered from recto-vaginal screening culture from 3 hospitals. S. agalactiae isolates showed susceptible MICs to erythromycin, MIC≤0.12mg/L, and azithromycin, MIC≤0.25mg/L, but resistant MICs to clindamycin, MIC=4mg/L, and lincomycin, MIC=64-128mg/L. Isolates were PCR positive for lnuB gene. Four clones were discriminated by ApaI-PFGE (n): A (3), B (1), C (1) and D (1). Here we describe for the first time the polyclonal emergence of S. agalactiae harboring the lnuB gene in Latin-America.